First insights into the microbiome of Tunisian Hyalomma ticks gained through nextgeneration sequencing with a special focus on H. scupense - Ben Yedem, Hayet; Lekired, Abdelmalek; Mhadhbi, Moez; Dhibi, Mokhtar; Romdhane, Rihab; Chaari, Soufiene; Rekik, Mourad; Ouzari, Hadda-Imene; Hajji, Tarek; Darghouth, Mohamed Aziz (Public Library of Science (PLOS ONE), 2023)
Ticks are one of the most important vectors of several pathogens affecting humans and animals. In addition to pathogens, ticks carry diverse microbiota of symbiotic and commensal microorganisms. In this study, we have investigated the first Tunisian insight into the microbial composition of the most dominant Hyalomma species infesting Tunisian cattle and explored the relative contribution of tick sex, life stage, and species to the diversity, richness and bacterial species of tick microbiome. In this regard, next generation sequencing for the 16S rRNA (V3-V4 region) of tick bacterial microbiota and metagenomic analysis were established. The analysis of the bacterial diversity reveals that H. marginatum and H. excavatum have greater diversity than H. scupense. Furthermore, microbial diversity and composition vary according to the tick’s life stage and sex in the specific case of H. scupense. The endosymbionts Francisella, Midichloria mitochondrii, and Rickettsia were shown to be the most prevalent in Hyalomma spp. Rickettsia, Francisella, Ehrlichia, and Erwinia are the most common zoonotic bacteria found in Hyalomma ticks. Accordingly, Hyalomma ticks could represent potential vectors for these zoonotic bacterial agents.